Improved eco-friendly barrier materials based on crystalline nanocellulose/chitosan/carboxymethyl cellulose polyelectrolyte complexes. (July 2018) - Chi, Kai; Catchmark, Jeffrey M.
Abstract: Sustainable, cost-effective and ecologically compatible materials derived from renewable natural resources have attracted a tremendous level of attention as replacements for a broad array of volume commercial materials based on petroleum-derived compounds. In the present study, we demonstrate ternary polysaccharide polyelectrolyte complex (PPC) materials consisting of crystalline nanocellulose (CNC), chitosan (CS) and carboxymethyl cellulose (CMC) produced via an immediate high-shear homogenization process. Ionically cross-linked CS and CMC behaved as the continuous matrix and CNC was incorporated as a nanoreinforcement. The developed PPC materials exhibited homogeneous, compact morphological features and enhanced mechanical and barrier properties, ascribed to the even distribution and good interfacial compatibility of CNC within the CS/CMC matrix. PPC films with 10 wt% CNC content showed tensile strength and Young's modulus of 60.6 MPa and 4.7 GPa, respectively, and water vapor transportation rate of 7982 g μm m −2 d −1 . In addition, PPC composites containing <5 wt% CNC performed as an excellent barrier coating against liquid (grease, water and oil) penetration on the paperboard substrate. These results indicate the potential of PPC materials as eco-friendly, bio-based barrier films or coatings for packaging applications. Graphical abstract: Image 1 Highlights: Ternary polysaccharide polyelectrolyte complexes (PPCs) were developed. Sustainable PPC barrier coatings were applied to the paperboard substrate. PPC coating showed excellent liquid (grease, water and oil) barrier performance. Addition of CNC notably improved the mechanical property and WVTR of PPC film. High levels of CNC addition degraded barrier performance of PPC material.